A Meta-Analysis of Using Protamine for Reducing the Risk of Hemorrhage During Carotid Recanalization: Direct Comparisons of Post-operative Complications - Pan, Yongli; Zhao, Zhiqiang; Yang, Tao; Jiao, Qingzheng; Wei, Wei; Ji, Jianyong; Xin, Wenqiang (Frontiers in Pharmacology, 2022)
Abstract Background: Protamine can decrease the risk of hemorrhage during carotid recanalization. However, it may cause severe side effects. There is no consensus on the safety and efficacy of protamine during the surgery. Thus, we conduct a comprehensive review and meta-analysis to compare the difference between using the protamine and no-protamine groups. Method: We systematically obtained literature from the Medline, Google Scholar, Cochrane Library, and PubMed electronic database. All four databases were scanned from 1937 when protamine was first adopted as a heparin antagonist until February 2021. The reference lists of identified researches were manually checked to determine other eligible studies that qualify. The articles were included in this meta-analysis as long as they met the criteria of PICOS, the conference or commentary articles, letters, case report or series, and animal observation were excluded from this study. The Newcastle-Ottawa Quality Assessment Scale and Cochrane Collaboration’s tool are used for assessing the risk of bias of each included observational study and RCT, respectively. Stata version 12.0 statistical software (StataCorp LP, College Station, Texas) was adopted as statistical software. When I2<50%, we consider the data has no obvious heterogeneity, and We conduct a meta-analysis using the fixed-effect model. Otherwise, the random-effect model was performed. Result: A total of 11 studies, which included 94618 participants, are included in this study. Our analysis found the rate of wound hematoma did a big difference among protamine and no-protamine patients (OR = 0.268, 95%CI = 0.093 to 0.774, P= 0.015). Furthermore, the incidence of hematoma requiring re-operation (0.7%) was significantly lower than patients without protamine (1.8%). However, there was no significant difference in the incidence of stroke, wound hematoma with hypertension, transient ischemic attacks (TIA), myocardial infarction (MI), and death. Conclusion: Among included participants undergoing recanalization, the use of protamine is effective in reducing hematoma without increasing the chances of other complications. Besides, more evidence-based performance is needed to supplement this opinion due to inherent limitations.